Geomorfologi Daerah Lombongo Dan Sekitarnya, Kecamatan Suwawa Tengah, Kabupaten Bone Bolango - Ruhimat, Nursultan Akbar; Arifin, Yayu Indriati; Kasim, Muh (Universitas Negeri Gorontalo, 2024)
The research area is located in Lombongo village and its surroundings which have interesting characteristics and landforms for research. This study aims to analyze and map geomorphological conditions to obtain information related to geomorphological aspects. The method used is geomorphological aspect analysis. The results of this study indicate that the geomorphological units of this area are intrusive mountains and alluvial plains. The geomorphological aspects of this area are divided into morphography consisting of mountain and lowland units, morphometry consisting of elevation points ranging from 0 - 750 masl, with a very steep slope, the morphogenesis of the research area is divided into active morphostructures, namely fractures and passive morphostructures, namely porphyry diorite, granodiorite and alluvial deposits, morphodynamics of the research area, namely river flow patterns consisting of dendritic and parallel flow patterns with mature to young river stages, based on the regional geological map, the morphochronology tilamuta sheet of the research area was formed in the Eocene - Holocene era, the morphoarrangement of the research area is in the form of a high erosion process.